UJI EFEKTIVITAS EKSTRAK PIROLISIS Nicotiana tabacum L. varVirginia TERHADAP BAKTERI Escherichia coli ATCC 25922 - Basra Ahmad Amru (2019)
ndonesia is a country with high production of tobacco and has different kind of varieties. At present, tobacco plants in Indonesia are most empowered as the main raw material for cigarettes. In addition, tobacco can also be empowered in herbal medicine because tobacco plants, especially on tobacco leaves, contain active compounds that are antimicrobial including flavonoid compounds, alkaloids, and terpenoids. This study aims to determine the effectiveness of inhibition of tobacco extract on the growth of Escherichia coli. This study uses an experimental research design with tobacco extract samples obtained from the Department of Chemical Engineering, University of Indonesia with concentrations of 20%, 40%, 60%, 80% and 100%. The antimicrobial test method used is the hole cup method in the Mueller Hinton Agar medium. One-Way ANOVA test results with p value = 0,000 indicate that there is an antimicrobial effectiveness of tobacco extract on the growth of Escherichia coli. The highest inhibition zone diameter was found at a concentration of 100%, which is 11.65 mm.